Viability of crowdfunding in the South African commercial real estate market . - Zwick, Elan (My University, 2016)
Crowdfunding can be defined as an open call for funding over the internet. This is done with the aid of an online portal which connects the investing crowd with the entrepreneur/deal sponsor in order to fund a project. The rapid growth and adoption of crowdfunding in the United States and Europe, combined with the relaxing of financial regulations in these countries, has given rise to equity-based crowdfunding, whereby an investor can contribute money in exchange for an equal portion of equity in a given project. Equity-based crowdfunding laid the foundation for commercial real estate crowdfunding which allows a large number of people to contribute small amounts of capital in exchange for an equity stake in a commercial property. Equity based crowdfunding and commercial real estate crowdfunding does not yet exist in the South African marketplace. A survey on the notion of commercial real estate crowdfunding was conducted to gain insight from commercial property professionals in the investment and development market in South Africa. An in-depth interview was also conducted with a financial and legal expert from Java Capital to provide understanding into the commercial property regulatory and securities environment in South Africa and where real estate crowdfunding could potentially fit into a South African context. The key findings of the survey suggest that both investors and developers of commercial real estate: (1) experience difficulty in raising bank finance and sourcing qualified investors, hence losing out on otherwise viable investment and development opportunities; (2) prefer different property types and attributes when purchasing or developing commercial real estate; (3) view the internet and its various online portals as an important asset when procuring new business. A key finding of the interview is that equity-based crowdfunding and commercial real estate crowdfunding has a long road to travel from a crowdfunding regulatory/legal framework to come into existence in South Africa. No legal framework exists yet for this type of investment platform. The closest connection to real estate crowdfunding would be the Collective Investment Schemes Act, Act 45 of 2002. This Act is governed by the auspices of the Financial Services Board and has the most stringent set of regulations compared to other Acts that govern the exchange of securities in the commercial property marketplace. Evidence from my research suggests that commercial real estate crowdfunding poses a big opportunity for the South African commercial real estate market. Although equity-based crowdfunding legislation is a long way from fruition in South Africa, government, together with the FSB must take the necessary steps to allow for such an investment platform to coexist alongside other investment vehicles. If crowdfunding, in all its various forms discussed in this research paper, is implemented and executed well, the benefits to South Africa are enormous. The main benefits include: stimulation of the economy and driving economic growth; providing entrepreneurs with an alternate access to capital; and ultimately creating jobs for the millions of unemployed people in the country.
MBA Thesis
Keywords: Crowd funding,Online social networks -- Economic aspects,Real estate business -- South Africa -- Finance.